Utilization of the “Koin” Media as a Representation of Natural Wealth in the Geopark Batur Museum on the Topic “My Region and Its Natural Wealth” for Fourth-Grade Elementary School Students - Ni Komang Novi Susanti Susanti; Gusti Ngurah Sastra Agustika; I Made Citra Wibawa (Jurnal Edutech Undiksha, 2025)
This study was motivated by the low learning outcomes of fourth-grade students in Science and Social Studies (IPAS), particularly on the topic “My Region and Its Natural Resources.” The purpose of this research was to develop, test the feasibility, and determine the effectiveness of the interactive comic media “KOIN: The Wonders of Natural Resources” as a learning tool to enhance students’ understanding and motivation. The research subjects consisted of 25 fourth-grade students and three experts, including a content expert, a learning design expert, and a media expert. The study employed a Research and Development (R&D) approach using the ADDIE development model, with data collected through multiple-choice tests, questionnaires, interviews, and observations. Data analysis included quantitative descriptive analysis, qualitative descriptive analysis, and inferential statistical analysis, including normality tests and paired-sample t-tests. The results indicated that the interactive comic media KOIN received validation scores from the experts above 90%, categorizing it as “very good,” and trials with individual students and small groups also yielded very good results. Effectiveness tests through pre-test and post-test analysis revealed a significant improvement in learning outcomes, evidenced by a paired-sample t-test result of tcalculated = 14.291 > ttable = 2.064 at a 5% significance level. These findings demonstrate that KOIN media is effective and feasible for IPAS learning, contributing to the development of interactive media and supporting teachers in implementing the Merdeka Curriculum based on context and technology.